Realities Behind Teachers’ Contextualization Practices in Teaching Araling Panlipunan - Antoni, Analie Macaroncio (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examines the realities behind teachers’ contextualization practices in teaching Araling Panlipunan within the Philippine basic education system. Grounded in a qualitative descriptive phenomenological approach, the study sought to understand how teachers conceptualize contextualization, how they enact it in classroom practice, and what challenges and enabling conditions shape its implementation. In-depth, semi-structured interviews were conducted with eleven junior high school Araling Panlipunan teachers from public secondary schools in the Alangalang District, Leyte Division. Findings reveal that teachers view contextualization as a process of relating lessons to learners lived experiences, local culture, and community realities, yet their actual practices vary widely depending on institutional demands, availability of resources, workload, and prior training. While teachers recognize the pedagogical value of contextualization in promoting engagement and meaningful learning, they encounter constraints such as limited time, insufficient localized materials, and frequent curricular adjustments. Despite these challenges, teachers demonstrate adaptive strategies and professional commitment, modifying lessons and drawing on community knowledge to sustain contextualized instruction. The study underscores the need for sustained professional development, consistent instructional guidance, and institutional support to strengthen contextualization practices. By highlighting teachers lived experiences, this research contributes to the discourse on culturally responsive and context-based pedagogy and supports Sustainable Development Goal 4 (Quality Education).